How Emerging Europe Came Through the 2008/09 Crisis : An Account by the Staff of the IMF's European Department - Bakker, Bas (International Monetary Fund, 2012)
Emerging Europe was particularly hard hit by the global financial crisis, but a concerted effort by local policymakers and the international community staved off impending financial meltdown and laid the foundations for renewed convergence with western Europe. This book, written by staff of the IMF's European Department that worked on the region at the time, provides a unique account of events: the origins of the crisis and the precrisis policy setting; the crisis trigger and the scramble to avoid the worst; the stabilization and recovery; the remaining challenges; and the lessons for the future. Five regional chapters provide the analytics to put events into perspective. Dedicated chapters for all 19 countries of the region dig deeper into the idiosyncrasies of each economy and provide extensive economic data. A final chapter distills the lessons from the overall regional experience and the wide intraregional diversity. Taken together, they make this book an indispensible reference for economic scholars of the region and beyond.